Truncal Acne Is Independently Associated with Stigmatization, Poorer Treatment Adherence and Greater Healthcare Utilization: A 20-country Survey - Marco Rocha; Valérie Mangeaut; Jean-Daniel Daumont; Virginie Ribet; Charles Taieb; Bruno Halioua (Acta Dermato-Venereologica, 2026)
Truncal acne (TA) affects 40–50% of adults with acne vulgaris and remains understudied despite its psychosocial impact. We aimed to evaluate the association of TA with stigmatization, psychosocial burden, healthcare utilization and treatment adherence, compared with exclusively facial acne (FA). We hypothesized that TA would be independently associated with greater psychosocial burden and healthcare utilization than FA alone. In this cross-sectional international online survey of 1,879 adults with physician-diagnosed acne (FA n=1,075; TA n=804) across 20 countries, multivariable logistic regression adjusted for age, sex and country showed that TA was independently associated with stigmatization (aOR 1.41 [95%CI 1.16–1.71]), hospitalization (aOR 1.73 [1.25–2.38]) and poor treatment adherence (aOR 1.26 [1.03 1.53]). Stigmatization was equally prevalent in truncal-only (49.2%) and combined facial-and truncal (50.5%) patients (aOR 1.00), indicating that it is intrinsic to truncal involvement rather than a consequence of facial disease. Truncal-only patients had lower dermatologist access (63.8% vs 78.9%) yet markedly higher hospitalization and surgical consultation rates. TA is independently associated with psychosocial burden and higher healthcare resource utilization; systematic trunk examination during acne consultations is warranted.